Systematic Literature Review : The Correlation Between Head of Room Leadership Style and Work Motivation of Nurse in the Hospital - Aji Ari Juanda; Heri Ridwan; Iyos Sutresna (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Leadership is the process of influencing or setting an example for followers through communication, with the aim of achieving organizational goals. The issue of nurse motivation in hospitals remains a current concern. This does not necessarily mean that nurses are underperforming, but it may be influenced by ineffective leadership, which can affect their level of work motivation. The objective of this research is to assess the correlation between the leadership style of ward heads and the work motivation of nurses in hospitals, as well as to identify the leadership styles commonly used by ward heads. The research method employed is systematic literature review. The research sample involves all practicing nurses in hospitals. The review of 11 research articles, spanning from 2018 to 2023 and originating from Indonesia, Timor-leste, and Jordan, indicates a correlation between the leadership style of ward heads and the work motivation of nurses in hospitals. The democratic leadership style is frequently used by ward heads in hospitals, as identified in the study.